(untitled) (Journal of actual problems of jurisprudence, 2016)
This article discusses qualification for judges under the laws of the Russian Federation. Author prepared a brief analysis of the current legislation of the Russian Federation regulating the issues of selection of judges . The necessity of increasing the requirements for the culture of behavior of law students . It is proposed to formalize it in law the concept of “ judicial career .” Based on the research also suggested to fix the Federal Law of the Russian Federation “On the Status of Judges “ rule mandating a candidate for judge of the degree of “ Master of Law “ , and that there is a long-felt need to raise the age limit for first-time applying for the post of judge .